Food Spectrum and Habitat-Specific Diets of Benthic Foraminifera From the Wadden Sea – A Fatty Acid Biomarker Approach - Haynert, Kristin; Gluderer, Franziska; Pollierer, Melanie M.; Scheu, Stefan; Wehrmann, Achim (Frontiers in Marine Science, 2020)
Tidal coasts are characterized by natural disturbances, forming a broad variety of habitats, which provide different niches and varying food resources for benthic foraminifera. Foraminifera occupy different trophic levels and fill key trophic positions in benthic food webs, but detailed studies on their nutrition spectrum in inter- to supratidal environments are lacking. Further, it is unknown to what extent foraminifera can switch between different feeding modes depending on resource availability in different Wadden Sea habitats. In order to shed light on these questions, we investigated potential food resources in sediments as well as the food spectrum of two dominant benthic foraminifera, Trochammina inflata and Ammonia tepida, in four characteristic habitats of the Wadden Sea: salt marsh, mixed flat, oyster reef and mud flat, using fatty acid (FA) analysis. The sediments of the four habitats provide a broad range of food sources including green algae, brown algae, diatoms and bacteria for benthic foraminifera. The FA profile of T. inflata from the salt marsh and mixed flat was dominated by green algae and bacteria, whereas the brown algae biomarker was only found in specimens from the salt marsh. In comparison, FA profiles of A. tepida suggested dominant algae feeding (green algae and diatoms), whereas brown algae and bacterial FAs were only found in specimens from the oyster reef. The results suggest that foraminifera mainly feed at low trophic levels with selective food intake closely depending on their habitat. The diverse nutritional strategies may allow efficient exploitation of resources in dynamic tidal habitats. Presumably, foraminifera serve as an important link between lower and higher trophic levels and thus fill key trophic positions in the benthic food web of the Wadden Sea.